Why Geographical Indications Can Support Sustainable Development in European Agri-Food Landscapes - Flinzberger, Lukas; Cebrián-Piqueras, Miguel A.; Peppler-Lisbach, Cord; Zinngrebe, Yves (Frontiers in Conservation Science, 2022)
Implementing the European Green Deal and transforming agricultural practices requires a wider and amplified policy toolbox. As many sustainability considerations are context-dependent, there is a need for instruments, which take individual characteristics of production landscapes into account. Food products with a particularly strong relationship to their landscape of origin can be marketed under the “Protected Designation of Origin” label (PDO). In this article, we analyze synergies between PDO production and regional sustainable development by assessing to what extent social-ecological landscape characteristics appear in landscapes with PDO-labeled food production systems. Building upon 12 social-ecological variables we defined three landscape characteristics influential for the presence of PDOs by using a principal component analysis. By running regression models combining those characteristic landscapes with the spatial distribution of PDO certification we were able to explore linkages between landscapes and products. Additionally, a geographically weighted regression delivered insights into the regional differences and product-specific relationships throughout the EU countries. Overall, we could prove the assumed positive correlation between PDO production and ecologically valuable landscapes. Further, we showed that mostly meat PDOs coincide with landscapes influenced by structural change, while cheese PDOs are not well captured by our models despite their large number. We can conclude that PDOs have the potential to jointly support conservation and rural development, especially when they would be tied to sustainable management standards in the future.